2020
DOI: 10.1073/pnas.2007495117
|View full text |Cite|
|
Sign up to set email alerts
|

Large enhancement of thermoelectric performance in MoS 2 / h -BN heterostructure due to vacancy-induced band hybridization

Abstract: Local impurity states arising from atomic vacancies in two-dimensional (2D) nanosheets are predicted to have a profound effect on charge transport due to resonant scattering and can be used to manipulate thermoelectric properties. However, the effects of these impurities are often masked by external fluctuations and turbostratic interfaces; therefore, it is challenging to probe the correlation between vacancy impurities and thermoelectric parameters experimentally. In this work, we demonstrate that n-type moly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…[ 39,42 ] Nevertheless, for the temperature region below 100 K, the mobility changes much slowly with decreasing temperature and the drastic decrease in Seebeck coefficient (Figure S7, Supporting Information) starts to dominated the PF trend. [ 50,51 ] Remarkably, the peak values of PF we observed for different gate voltage are almost overlapped with the onset transition temperatures between piezoelectric scattering and polar optical phonon scattering and shows a sensitive dependence to gate voltage (i.e., shifts from under 80 K to 200 K for −10 and 70 V gate voltage, respectively) as shown in Figure 4b. This is ascribed to the fact that increasing V g results in higher carrier concentration (Figure S8, Supporting Information) in Bi 2 O 2 Se, which increases the contribution of screening effect and effectively suppress the POP scattering, therefore shifting the mobility of POP regime to higher values.…”
Section: Figurementioning
confidence: 59%
See 1 more Smart Citation
“…[ 39,42 ] Nevertheless, for the temperature region below 100 K, the mobility changes much slowly with decreasing temperature and the drastic decrease in Seebeck coefficient (Figure S7, Supporting Information) starts to dominated the PF trend. [ 50,51 ] Remarkably, the peak values of PF we observed for different gate voltage are almost overlapped with the onset transition temperatures between piezoelectric scattering and polar optical phonon scattering and shows a sensitive dependence to gate voltage (i.e., shifts from under 80 K to 200 K for −10 and 70 V gate voltage, respectively) as shown in Figure 4b. This is ascribed to the fact that increasing V g results in higher carrier concentration (Figure S8, Supporting Information) in Bi 2 O 2 Se, which increases the contribution of screening effect and effectively suppress the POP scattering, therefore shifting the mobility of POP regime to higher values.…”
Section: Figurementioning
confidence: 59%
“…c) The dependence of µ on T shows two pronounced temperature regime consistent with the transition of dominant scattering mechanism from piezoelectric scattering to POP scattering. From 20 to 200 K, µ 1 follows a μ ~ T −0.47 dependence and µ 2 follows a μ ~ T −4.58 dependence above ≈200 K. d) The value of γ in Bi 2 O 2 Se is much larger compared to other reported 2D materials (MoS 2 , [ 50 ] PdSe 2 , [ 49 ] black phosphorus, [ 53 ] WSe 2 , [ 54 ] WS 2 [ 55 ] ).…”
Section: Figurementioning
confidence: 92%
“…[ 6,7 ] Recently, graphene‐inspired layered 2D materials have rapidly emerged in the TE research community due to their unique electronic band structure and quantum confinement effect [ 8,9 ] as well as gate‐tunable carrier concentrations, factors which are lacking in conventional bulk TE solids. For example molybdenum disulfide (MoS 2 ), as a representative and more commercialized transition metal dichalcogenide (TMD) in the 2D material family, has been investigated to show promising TE properties, and has a record power factor (PF) of 50 mW m −1 K −2 induced by its special band hybridization [ 10,11 ] at low temperature. However, 2D semiconductors which are predominantly of hexagonal structure normally exhibit relatively high thermal conductivity, which is an impediment to the achievement of high ZT , rendering such materials less competitive compared to bulk solids like lead telluride [ 2,3 ] and tin selenide, [ 12,13 ] to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the high PF with the large thermal conductivity of both graphene and boron nitride, this work by Duan and co-workers demonstrated that the graphene/hBN heterostructure can be a very promising material for active cooling of electronics. Wu and coworkers [224] fabricated MoS2/hBN heterostructure samples with sulfur vacancies and measured the in-plane thermoelectric properties using a similar approach as in Ref. [5].…”
Section: In-plane Transportmentioning
confidence: 99%
“…The n-type MoS2 on hBN exhibited an extremely large positive Seebeck coefficient of 2 mV/K in the on-state because of the magnetically induced Kondo effect. [224] Further, by tuning the chemical potential, Wu et al measured a PF as high as 50 mW/m • K 2 at 30K or PFT value of 1.5 W/mK. By combining the nanostructuring and stacking approaches, Oh and co-workers [219] fabricated sub-20 nm GNR arrays on monolayer MoS2.…”
Section: In-plane Transportmentioning
confidence: 99%